Penggunaan Media Audio Visual Berpengaruh Terhadap Penguasaan Jurus Tunggal Pencak Silat - wilda .; Hendri Irawadi (Jurusan Kepelatihan, Fakultas Ilmu Keolahragaan, Universitas Negeri Padang, 2019)
The problem of this research is that many pencak silat learners do not memorize a single martial arts stance. This study aims to determine the effect of the use of audio-visual media on the mastery of a single martial arts stance of Al-Istiqamah West Pasaman High School Students. This type of research is experimental. The time of the study was carried out on 19 June - 25 July 2018 at Al-Istiqamah West Pasaman High School. This sampling technique is by purposive sampling of 16 students (12 men and 4 women). Data analysis of the results of t test data processing obtained t count> t table (9.53> 1,753). The average value of mastery single martial arts after being given the audio visual media method is higher that is 378.69 compared to the average value before using audio visual media that is equal to 297.75. The results of the analysis show that there is an influence of the use of audio-visual media on the mastery of a single martial arts stance of Al-Istiqamah West Pasaman High School